Mapping knowledge structure and global status of sarcopenia in geriatric hip fractures: A bibliometric and visualized study - Zhao, Zhibang; Fan, Wenliang; Chu, Qingbo (Frontiers in Surgery, 2022)
Background: Sarcopenia in the geriatric hip fracture is attracting increased attention in recent years. This study aimed to explore the bibliometric characteristics and current status of sarcopenia research in hip fracture of the elderly. Methods: Publications related to sarcopenia in geriatric hip fracture published between January 2000 and July 2022 were extracted from the Science Citation Index Expanded, and bibliometric and visualized studies were performed by VOSviewer, Citespace, and R. Results: The 1223 articles used in our study were written by 6326 authors from 1879 organizations in 60 countries, published in 388 journals, and cited 37198 references from 5422 journals. The USA contributed the most publications (288 publications). The journal with the largest number of papers was Osteoporosis International (62 publications), and the Journals of Gerontology Series A - Biological Sciences and Medical Sciences had been more cited than any other journals in this field (3302 citations). The University of Melbourne published the biggest number of papers (72 publications) focusing on sarcopenia in elderly hip fractures while the California Pacific Medical Center Research Institute had the largest citations (4239 citations). Cawthon PM was the most productive and influential author in the field. keywords were classified into 6 clusters: Cluster 1 (sarcopenia in aging), Cluster 2 (osteoporosis), Cluster 3 (bone density), Cluster 4 (body composition), Cluster 5 (physical performance), and Cluster 6 (risk factor). Conclusion: Geriatric hip fracture is one of the most significant health issues in the aging society. In the past 20 years, an increasing number of studies were performed to explore the relationship between sarcopenia and hip fracture in the elderly. The USA showed the strongest influence in this field, including publication numbers, citations, institutions, funding agencies, and authorship. Sarcopenia in aging, osteoporosis, bone density, body composition, physical performance, and risk factor may become the future hotspots in this field.